2008
DOI: 10.1042/bsr20080079
|View full text |Cite
|
Sign up to set email alerts
|

In vitro characterization of native mammalian smooth-muscle protein synaptopodin 2

Abstract: An analysis of the primary structure of the actin binding protein fesselin revealed it to be the avian homologue of mammalian synaptopodin 2 1 [Schroeter, Beall, Heid, and Chalovich (2008) Biochem. Biophys. Res. Commun. 371, 582-586]. We isolated synaptopodin 2 from rabbit stomach and showed that it shared several key functions with fesselin. Both fesselin and synaptopodin 2 bound to Ca2+-calmodulin, α–actinin, and smooth muscle myosin. In addition, both proteins stimulated the polymerization of actin in a Ca2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…In regard to nicotine, Phox2A regulates transcription of the α3 nAChR gene (69), but its role in the pancreas has not yet been elucidated. SYNPO2 has actin-binding activity and shuttles between the nucleus and the cytoplasm in a stress-induced manner (70). This protein has been studied in neurons, but no evidence is available supporting its function in the pancreas.…”
Section: Resultsmentioning
confidence: 99%
“…In regard to nicotine, Phox2A regulates transcription of the α3 nAChR gene (69), but its role in the pancreas has not yet been elucidated. SYNPO2 has actin-binding activity and shuttles between the nucleus and the cytoplasm in a stress-induced manner (70). This protein has been studied in neurons, but no evidence is available supporting its function in the pancreas.…”
Section: Resultsmentioning
confidence: 99%
“…Here, the analysis revealed additional genes that had not previously been associated with atherosclerosis, of which several were selected for replication in a nonoverlapping set of patients. LMOD1 (Leiomodin 1) has been predicted to be an SMC-specific gene [64] and an SRF/ MYOCD-dependent transcript [65] and SYNPO2 (Synaptopodin 2) was predicted to be associated with SMC cytoskeletal organization [66]. Because LMOD1 and SYNPO2 were strongly downregulated in plaques and correlated with all markers of differentiated SMCs, they may represent novel markers of SMC phenotype and should be explored in the context of SMC function in atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent in vitro studies indicated that avian myopodin accelerates actin nucleation, polymerization and bundling (1820), that rabbit myopodin promotes actin polymerization (21), and that human myopodin can directly bundle actin filaments (9). While these in vitro studies implicated human myopodin as a potential regulator of the actin cytoskeleton, there was no direct evidence in support of this conjecture.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the nomenclature in the field has become confusing. Myopodin has variously been referred to as fesselin (2), genethonin (3), myopodin (1, 4, 8, 39) and, more recently, synaptopodin 2 (21). All of these studies refer to the ΔN‐MYO1 isoform in the present report.…”
Section: Discussionmentioning
confidence: 99%